2011
DOI: 10.1007/s13165-011-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ley duration on the yield and quality of the subsequent cereal crop (spring oats) in an organically managed long-term crop rotation experiment

Abstract: The ability to maintain crop yield and quality in systems based on nitrogen (N) fixed by legumes rather than from synthetic N fertilisers is fundamental to the long-term viability of organic farming. This paper reports crop yield and nitrogen uptake parameters for the first spring oat crop after grass/clover ley in organically managed ley/arable rotations to indicate the amount of fertility built-up during the ley period. The trial site, at Tulloch in North East Scotland, underwent two complete cycles of 6-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Following land use change or within rotational systems, there may be a release of mineral N from the organic N pool due to tillage, providing a substrate for nitrification-and denitrification-driven N 2 O release. In organic farming systems this build-up of organic N within the grassland phase of a rotation is used to provide nutrients (particularly N) for subsequent arable crops (Stockdale et al, 2001;Watson et al, 2011). This can lead to some high emissions in individual years from organic farming systems, particularly where the system exists in mild and wet climates such as that at Scottish organic site at Tulloch (despite no apparent input of N in that year).…”
Section: Discussionmentioning
confidence: 99%
“…Following land use change or within rotational systems, there may be a release of mineral N from the organic N pool due to tillage, providing a substrate for nitrification-and denitrification-driven N 2 O release. In organic farming systems this build-up of organic N within the grassland phase of a rotation is used to provide nutrients (particularly N) for subsequent arable crops (Stockdale et al, 2001;Watson et al, 2011). This can lead to some high emissions in individual years from organic farming systems, particularly where the system exists in mild and wet climates such as that at Scottish organic site at Tulloch (despite no apparent input of N in that year).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggesting oat as a good LGS exploiter are confirmed by their results [28]. Especially in the oat/plough test method and in the damp hollows, oats were able to take up high levels of mineralised LGS nitrogen in spring (up to 105 kg N ha −1 ).…”
Section: Winter Wheat Following Oatmentioning
confidence: 63%
“…By inserting oats, the N-deployment from organic plant matter (decomposed LGS residuals, straw and oat root residues) is more in sync with winter wheat N up-take the following spring. The advantages of oat as an LGS subsequent crop are its extensive root system and high nutrient up-take [28], while as a winter wheat preceding crop, oat's vegetative growth suppresses weeds. As a recovery crop, oat prevents the spreading of fungal pathogens, such as black root rot (Gaeumannomyces graminis) [29,30].…”
Section: Winter Wheat Following An Oat Cropmentioning
confidence: 99%
“…Soils data from each site were collected from project reports, site records and published literature (Haggar and Padel, 1996; Lennartsson, 2000; Welsh et al, 2002; Cormack, 2006; Taylor et al, 2006). The bulked soil samples at each site were taken along a W transect twice each year in the case of Elm Farm (Welsh et al, 2002), Warwick University (Lennartsson, 2000) and ADAS Terrington (Cormack, 2006) (after sowing and harvest) and once per year at the SRUC sites (Watson et al, 2011) and at Ty Gwyn (Haggar and Padel, 1996) (January and April, respectively). Samples were analyzed for available P (Modified Morgan's solution at SRUC sites and Olsen's method at other sites), available K (Modified Morgan's solution at SRUC sites and ammonium nitrate extraction at ADAS and Elm Farm), mineral N (potassium chloride solution) and organic matter (loss on ignition).…”
Section: Methodsmentioning
confidence: 99%